(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes the transformation of linguistic practices in the information society. The aim of the study is to identify the main changes in the structure, functions, and pragmatic characteristics of communication under the influence of digital technologies. The methodological framework is based on the principles of information society theory (Manuel Castells), the concept of post-industrial development (Daniel Bell), and media communication theory (Marshall McLuhan). The article employs methods of discursive, pragmatic, and sociolinguistic analysis. The results demonstrate a shift in the genre structure of communication, the emergence of hybrid texts, the increasing role of visual-verbal codes, and the transformation of norms of linguistic politeness. A conclusion is drawn about the emergence of a new digital communication paradigm.